High-rate electrolyte, lithium ion battery containing high-rate electrolyte and electric equipment
By adding vinyl sulfate, difluoromethylphenylsulfone and nitrophthalocyanine dilithium to the electrolyte of the lithium-ion battery, the problem of lithium-ion battery is solved during the large-scale charge and discharge cycle, and the charging and discharge performance and safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411972637.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
During the large-scale charging and discharging cycle of existing lithium-ion batteries, lithium-ion batteries are prone to lithium extraction, resulting in faster electrolyte consumption, shortened battery life, and poor charging and discharging performance.
A high-rate electrolyte is used, which contains lithium salts, non-aqueous organic solvents and additives, among which the additives include vinyl sulfate, difluoromethylphenyl sulfone and dilithium nitrophthalocyanine, and the mass proportion of dilithium nitrophthalocyanine is 0.5% to 5%.
It effectively improves the battery's high-speed charging and discharging performance, reduces the accumulation of side reactions of the electrolyte on the surface of the positive electrode material, and improves the battery's circulation and safety performance.
Smart Images

Figure CN119764570A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-rate electrolyte, a lithium ion battery containing the same, and electrical equipment. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital products, electric vehicles, military and aerospace fields due to their high operating voltage, high energy density, long cycle life and environmental friendliness. With the popularization and application of smart digital products and the widespread application of new energy vehicles, people have a more urgent demand for fast charging performance of batteries. There are many factors that affect fast charging, including the design of positive and negative electrode materials and electrolytes. Among them, the electrolyte, as the "blood" system of lithium-ion batteries, is in contact with the positive and negative electrodes and the diaphragm. It is an important medium for transmitting lithium ions between the positive and negative electrodes. The performance of the electrolyte has a key influence on fast charging and discharging.
[0003] Among the current lithium-ion battery products, high-rate charge and discharge performance is poor, no electricity can be discharged at high rates, and lithium deposition occurs during high-rate charge and discharge cycles. Especially during high-rate charge and discharge cycles, lithium deposition is likely to occur on the surface of the negative electrode. The enriched metallic lithium will further consume the electrolyte, thereby exacerbating the battery life. Therefore, the need to improve the rate charge and discharge performance of lithium-ion batteries is imminent. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, embodiments of the present invention provide a high-rate electrolyte, a lithium-ion battery containing the same, and an electrical device.
[0006] In a first aspect, the present invention proposes a high-rate electrolyte, comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises vinylene sulfate, difluoromethylphenyl sulfone and dilithium nitrophthalocyanine, wherein the mass proportion of the dilithium nitrophthalocyanine in the electrolyte is 0.5% to 5%.
[0007] Furthermore, the preparation process of dilithium nitrophthalocyanine comprises the following steps:
[0008] Anhydrous n-pentane and 4-nitrophthalonitrile were mixed and stirred until dissolved, and then dilithium phthalocyanine and DBU were added to react under constant temperature reflux under the protection of inert gas;
[0009] After the reaction is completed, the mixture is cooled to room temperature, methanol is added, the mixture is allowed to stand and filtered, refluxed with acetone and filtered, and washed with methanol, chloroform and acetone in sequence until the filtrate is colorless, and purified nitrophthalocyanine dilithium is obtained by filtration.
[0010] Furthermore, the dilithium nitrophthalocyanine is Figure 2shown.
[0011] Furthermore, the mass proportions of the vinylene sulfate and the difluoromethylphenyl sulfone in the electrolyte are both within 2%.
[0012] Furthermore, the non-aqueous organic solvent includes a cyclic carbonate solvent and a linear carbonate solvent.
[0013] Furthermore, the cyclic carbonate solvent includes one or more of ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate, and the linear carbonate solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methylpropyl carbonate.
[0014] Furthermore, the concentration of the lithium salt in the electrolyte is 0.8-1.3 mol / L.
[0015] Further, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluorooxalatophosphate.
[0016] In a second aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the high-rate electrolyte provided in the first aspect.
[0017] In a third aspect, the present invention provides an electrical device comprising the lithium-ion battery provided in the second aspect.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] The present invention effectively improves the high-rate charge and discharge performance of the battery by adding vinylene sulfate, difluoromethylphenylsulfone and dilithium nitrophthalocyanine into the electrolyte, while reducing the accumulation of side reactions of the electrolyte on the surface of the positive electrode material, thereby improving the cycle performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0021] Figure 1 This is a diagram of the preparation process of dilithium nitrophthalocyanine of the present invention;
[0022] Figure 2 It is a structural diagram of dilithium nitrophthalocyanine of the present invention. DETAILED DESCRIPTION
[0023] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0024] The high-rate electrolyte, the lithium-ion battery containing the high-rate electrolyte and the electrical equipment provided by the present invention are specifically described below.
[0025] The high-rate electrolyte includes a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive includes vinylene sulfate, difluoromethylphenylsulfone and dilithium nitrophthalocyanine, wherein the mass proportion of the dilithium nitrophthalocyanine in the electrolyte is 0.5% to 5%.
[0026] Among them, the non-aqueous organic solvent includes a cyclic carbonate solvent and a linear carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate (EC), vinylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate, and the linear carbonate solvent includes one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and methyl propyl carbonate (MPC).
[0027] In some embodiments, the mass percentage of the non-aqueous organic solvent in the electrolyte is 75% to 80%.
[0028] In some embodiments, the concentration of the lithium salt in the electrolyte is 0.8 to 1.3 mol / L. The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluorooxalatophosphate.
[0029] The additives include vinylidene sulfate, difluoromethylphenyl sulfone and dilithium nitrophthalocyanine. The additive combination of vinylidene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PcNO2) can effectively improve the high-rate charge and discharge performance of the battery, while reducing the accumulation of side reactions of the electrolyte on the surface of the positive electrode material, and can improve the battery's cycle performance and safety performance.
[0030] Among them, vinyl sulfate DTD can improve the battery cycle performance, and increasing its content will deteriorate the impedance. Difluoromethylphenyl sulfone (DPS) has a low oxidation potential and can form a dense and stable interface film on the positive electrode surface during the first charge and discharge process, optimizing the positive electrode surface film and inhibiting the surface activity of the electrode, thereby inhibiting further contact between the electrolyte and the electrode active material and the formation of HF, reducing the oxidation and decomposition of the main solvent of the electrolyte on the electrode surface. At the same time, the sulfone group in the additive can effectively improve the conductivity of carbonate electrolytes, the fluorine-based functional group can participate in the formation of components such as LiF on the surface film, and the phenyl group can improve the stability of the electrolyte.
[0031] The structural formula of dilithium nitrophthalocyanine is Figure 2 As shown in Figure 2, lithium nitrophthalocyanine (Li2PcNO2) interacts with the solvent to form an obvious solvation sheath around the phthalocyanine ligand, which weakens the dipole-dipole interaction of the solvent, promotes the solvation of anions in the outer solvation sheath, inhibits the migration of anions, and increases the Li + transfer number, and at the same time promoted the dissociation of the solute, obtained higher ionic conductivity, and at the same time the homogenized Li + The flow alleviates the generation of local polarization and hinders the growth of dendrites. In addition, the -NO2 group on the substituent has strong chemical stability and cannot be destroyed by general chemical reactions. It can exist in the electrolyte for a long time. Since the -NO2 not in the conjugated system can rotate freely, the phthalocyanine molecules have steric hindrance, which can effectively reduce the crystallization and agglomeration phenomenon during long-term storage in the electrolyte.
[0032] In some embodiments, the mass proportions of the vinylene sulfate and the difluoromethylphenyl sulfone in the electrolyte are both within 2%.
[0033] In some embodiments, the mass proportion of dilithium nitrophthalocyanine in the electrolyte is 0.5% to 5%. The mass proportion of dilithium nitrophthalocyanine in the electrolyte can be 0.5%, 1%, 2%, 3%, 4%, 5%, or a value within a range consisting of any two values.
[0034] In some embodiments, Figure 1 As shown, the preparation process of dilithium nitrophthalocyanine includes the following steps: mixing anhydrous n-pentane and 4-nitrophthalonitrile and stirring until dissolved, adding dilithium phthalocyanine and DBU, and reacting under constant temperature reflux under the protection of inert gas; after the reaction is completed, cooling to room temperature, adding methanol, standing and filtering, refluxing and filtering with acetone, and washing with methanol, chloroform and acetone in turn until the filtrate is colorless, and filtering to obtain purified dilithium nitrophthalocyanine.
[0035] The inert gas may be nitrogen or argon.
[0036] In some embodiments, 15 ml of anhydrous n-pentane and 4.8 mol of 4-nitrophthalonitrile are added to a 100 ml round-bottom flask equipped with a magnetic stirring device, a reflux device, and a nitrogen protection device, and stirred until dissolved, and then 2.4 mol of lithium phthalocyanine (Li2PC) and 0.6 ml of DBU (1,8-diazabicycloundec-7-ene) are added. The mixture is refluxed at a constant temperature of 150 ° C for 5 hours under nitrogen protection. After the reaction is completed, it is cooled to room temperature, 60 ml of methanol is added to the mixture, and it is allowed to stand for 24 hours, filtered, refluxed with acetone for 1.5 hours, filtered, and washed with methanol, chloroform, and acetone in turn until the filtrate is colorless. Then it is pumped to dryness with an oil pump to obtain purified lithium nitrophthalocyanine.
[0037] The present invention is described below in conjunction with specific examples. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0038] Example 1
[0039] Prepare electrolyte:
[0040] Add 15ml of anhydrous n-pentane and 4.8mol of 4-nitrophthalonitrile to a 100ml round-bottom flask equipped with a magnetic stirring device, a reflux device, and a nitrogen protection device, stir until dissolved, and then add 2.4mol of lithium phthalocyanine (Li2PC) and 0.6ml DBU (1,8-diazabicycloundec-7-ene). Reflux at 150℃ for 5h under nitrogen protection. After the reaction is completed, cool to room temperature, add 60ml of methanol to the mixture, let it stand for 24h, filter, reflux with acetone for 1.5h, filter, and wash with methanol, chloroform, and acetone in turn until the filtrate is colorless. Then use an oil pump to pump to dryness to obtain purified lithium nitrophthalocyanine.
[0041] Cyclic carbonate solvent ethylene carbonate (EC), linear carbonate solvent ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of EC:EMC:DEC=3:5:2, and purified by molecular sieves, calcium hydride and lithium hydride to remove impurities and water to obtain a mixed solvent; at room temperature, conductive lithium salt LiPF6 is dissolved in the mixed solvent obtained above, the final concentration of the conductive lithium salt is 1.2 mol / L, and stirred evenly to obtain a common electrolyte.
[0042] Vinyl sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are added to the ordinary electrolyte prepared above, with the usage amount being 1%, 0.5% and 0.5% of the electrolyte mass respectively, to obtain a high-rate electrolyte with fast charging function for lithium-ion batteries.
[0043] Preparation of positive electrode:
[0044] 95% of lithium iron phosphate, 2% of positive electrode binder polyvinylidene fluoride and 3% of positive electrode conductive agent conductive carbon black were weighed by mass. First, polyvinylidene fluoride was added to N-methylpyrrolidone solvent (solid content was 10%) and put into a double planetary mixer, and stirred at a speed of 3000m / s for 2h to make a glue solution. Then, conductive carbon black was added to the above glue solution, and stirred at a speed of 5000m / s for 1h until it was uniform. Then, lithium iron phosphate was added to the above slurry, and stirred at a speed of 3000m / s for 3h until it was uniform. Finally, the slurry was coated on the current collector Al foil (coating thickness 200μm), and the positive electrode sheet was prepared after drying at a temperature of 100°C, and small positive electrode sheets were obtained by rolling and slitting.
[0045] Preparation of negative electrode sheet:
[0046] 96% of graphite negative electrode material, 1.2% of negative electrode binder sodium carboxymethyl cellulose, 1.8% of negative electrode binder styrene butadiene rubber and 1% of negative electrode conductive agent conductive carbon black were weighed by mass. First, sodium carboxymethyl cellulose was added to deionized water (solid content was 6%), put into a double planetary mixer, and stirred at a speed of 1000m / s for 5h to make a glue solution. Then, conductive carbon black and graphite were added to the above glue solution, stirred at a speed of 3000m / s for 3h until it was uniform, and then styrene butadiene rubber was added to the above slurry, stirred at a speed of 600m / s for 1h until it was uniform; finally, the slurry was coated (coating thickness 150μm) on the current collector Cu foil, and dried at 80°C to prepare a negative electrode sheet; and small negative electrode sheets were obtained by rolling and slitting.
[0047] Preparation of lithium-ion batteries:
[0048] The positive and negative electrode sheets are vacuum baked, and the positive electrode sheet, the separator (PE porous polymer film), and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. After stacking, the battery core (405059) is made and encapsulated in an aluminum-plastic film. After the baked battery core is injected, formed, aged, and divided into different capacities, the preparation of the lithium-ion battery is completed.
[0049] Example 2
[0050] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are 1%, 1% and 2% of the electrolyte mass, respectively.
[0051] Example 3
[0052] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are 1%, 1% and 5% of the electrolyte mass, respectively.
[0053] Example 4
[0054] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are 1%, 2% and 2% of the electrolyte mass, respectively.
[0055] Example 5
[0056] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are 1%, 2% and 5% of the electrolyte mass, respectively.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are not added to the electrolyte.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD) and difluoromethylphenyl sulfone (DPS) used are 1% and 2% of the mass of the electrolyte, respectively.
[0061] Comparative Example 3
[0062] The difference from Example 1 is that in the high-rate electrolyte, the amounts of vinylene sulfate (DTD), difluoromethylphenyl sulfone (DPS) and dilithium nitrophthalocyanine (Li2PCNO2) are 1%, 2% and 7% of the electrolyte mass, respectively.
[0063] Test Example 1
[0064] The electrolyte solutions and lithium ion batteries in Examples 1 to 5 and Comparative Examples 1 to 3 were tested for electrolyte viscosity and alternating current resistance (ACR). The test results are shown in Table 1 below.
[0065] Among them, ACR is the detection of AC resistance. The detection equipment is: JX-008 battery internal resistance tester. The test method is: add a fixed frequency of 1KHz to the tested battery cell, sample the voltage, and calculate the resistance value through the rectifier.
[0066] The viscosity of the electrolyte is tested using a DRT-1102D viscosity tester to test the viscosity of the prepared electrolyte.
[0067] Table 1:
[0068] plan Viscosity at 25℃(mPa.S) ACR at 25℃(mΩ) Example 1 0.889 0.41 Example 2 0.891 0.4 Example 3 0.903 0.45 Example 4 0.896 0.42 Example 5 0.913 0.46 Comparative Example 1 0.862 0.48 Comparative Example 2 0.886 0.44 Comparative Example 3 0.915 0.47
[0069] From Table 1 we can see that:
[0070] At 25°C, the viscosity of Examples 1 to 5 and Comparative Examples 1 to 3 is not much different, and the viscosity is mainly related to the solvent composition; the ACR test results at 25°C show that adding a certain amount of vinyl sulfate (DTD), difluoromethylphenyl sulfone (DPS) and lithium nitrophthalocyanine (Li2PCNO2) is beneficial to improving the internal resistance of the battery.
[0071] Test Example 2
[0072] The lithium ion batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to a room temperature cycle test, and the capacity retention rates after 700 cycles are shown in Table 2 below.
[0073] The test method is: the charge cut-off voltage is 3.65V, the discharge cut-off voltage is 2.0V, at 25°C, the battery to be tested is first charged at 0.5C and discharged at 1C, and the 1C discharge capacity C1 is measured; then the battery to be tested is charged at 2C and discharged at 2C for 700 cycles at 25°C, the discharge capacity of the 700th cycle is C2, and the calculation formula of the cycle capacity retention rate is: C2 / C1×100%. .
[0074] Table 2:
[0075] plan 2C / 2C cycle 700 cycles capacity retention rate Example 1 92.45% Example 2 91.32% Example 3 91.23% Example 4 90.68% Example 5 89.56% Comparative Example 1 83.67% Comparative Example 2 86.57% Comparative Example 3 84.05%
[0076] It can be seen from Table 2 that the cycle performance of Examples 1 to 5 is better than that of Comparative Examples 1 to 3. It can be seen that adding an appropriate amount of vinyl sulfate (DTD), difluoromethylphenyl sulfone (DPS) and lithium nitrophthalocyanine (Li2PCNO2) can make the battery cycle well under high-rate charge and discharge conditions. The main reason is that lithium nitrophthalocyanine (Li2PCNO2 can effectively inhibit the migration of anions and increase the Li + The transfer number is increased, and the dissociation of the solute is promoted, thereby obtaining a higher ionic conductivity and increasing the rate performance. At the same time, difluoromethylphenyl sulfone (DPS) can inhibit the surface activity of the electrode, thereby inhibiting the further contact between the electrolyte and the electrode active material and the formation of HF, reducing the oxidative decomposition of the main solvent of the electrolyte on the electrode surface, and enhancing the interface stability of the battery during the cycle.
[0077] Test Example 3
[0078] Safety performance tests were performed on the lithium ion batteries prepared in Examples 1 to 5 and Comparative Examples 1 to 3. The test results are shown in Table 3. The safety performance tests were performed according to the test requirements of the standards (GB / T 31485-2015 and GB 31241-2014).
[0079] Table 3:
[0080]
[0081]
[0082] It can be seen from Table 3 that adding appropriate amounts of vinyl sulfate (DTD), difluoromethylphenyl sulfone (DPS) and lithium nitrophthalocyanine (Li2PCNO2) can make the battery obtain good safety performance. The main reason is that lithium nitrophthalocyanine (Li2PcNO2) interacts with the solvent to form an obvious solvation sheath around the phthalocyanine ligand, which weakens the dipole-dipole interaction of the solvent, promotes the solvation of anions in the outer solvation sheath, and inhibits the Li + The flow alleviates the generation of local polarization and hinders the growth of dendrites. At the same time, the -NO2 group on the substituent has strong chemical stability, and the -NO2 not in the conjugated system can rotate freely, which makes the phthalocyanine molecules have steric hindrance and can effectively reduce the crystallization and agglomeration during long-term storage in the electrolyte.
[0083] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0084] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0085] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A high rate electrolyte, characterized in that: The invention comprises a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive comprises vinylene sulfate, difluoromethylphenyl sulfone and dilithium nitrophthalocyanine, wherein the mass proportion of the dilithium nitrophthalocyanine in the electrolyte is 0.5% to 5%.
2. The high rate electrolyte according to claim 1, characterized in that The preparation process of dilithium nitrophthalocyanine comprises the following steps: Anhydrous n-pentane and 4-nitrophthalonitrile were mixed and stirred until dissolved, and then dilithium phthalocyanine and DBU were added to react under constant temperature reflux under the protection of inert gas; After the reaction is completed, the mixture is cooled to room temperature, methanol is added, the mixture is allowed to stand and filtered, refluxed with acetone and filtered, and washed with methanol, chloroform and acetone in sequence until the filtrate is colorless, and purified nitrophthalocyanine dilithium is obtained by filtration.
3. The high rate electrolyte according to claim 1, characterized in that The mass proportions of the vinylene sulfate and the difluoromethylphenyl sulfone in the electrolyte are both within 2%.
4. The high rate electrolyte according to claim 1, characterized in that The non-aqueous organic solvent includes a cyclic carbonate solvent and a linear carbonate solvent.
5. The high rate electrolyte according to claim 4, characterized in that The cyclic carbonate solvent includes one or more of ethylene carbonate, vinylene carbonate, fluoroethylene carbonate, and difluoroethylene carbonate; the linear carbonate solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methylpropyl carbonate.
6. The high rate electrolyte according to claim 1, characterized in that The concentration of the lithium salt in the electrolyte is 0.8-1.3 mol / L.
7. The high rate electrolyte according to claim 1, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonylimide), lithium bis(fluorosulfonylimide), lithium difluorophosphate, lithium difluorobis(oxalatophosphate), and lithium tetrafluorooxalatophosphate.
8. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the high-rate electrolyte according to any one of claims 1 to 7.
9. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 8.
Citation Information
Patent Citations
Electrolyte containing phthalocyanine compound as well as preparation method and application of electrolyte
CN116014239A
Nonaqueous electrolyte secondary battery
JP2012174465A
Ion conducting electrolyte material
US5932133A
Class of solid-state electrolytes for rechargeable lithium batteries
US8974974B1